2021
DOI: 10.1152/physiol.00027.2020
|View full text |Cite
|
Sign up to set email alerts
|

Force Steadiness: From Motor Units to Voluntary Actions

Abstract: Voluntary actions are controlled by the synaptic inputs that are shared by pools of spinal motor neurons. The slow common oscillations in the discharge times of motor units due to these synaptic inputs are strongly correlated with the fluctuations in force during submaximal isometric contractions (force steadiness) and moderately associated with performance scores on some tests of motor function. However, there are key gaps in knowledge that limit the interpretation of differences in force steadiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 144 publications
6
132
0
Order By: Relevance
“…In recent years, decomposition of a surface EMG into contributions of individual MUs enabled analysis of neural coding in relatively large populations of MUs, and, consequentially, many new insights into the neurophysiology of the motor system [1], [3]- [8]. However identification of individual MUs from a surface EMG is not a trivial task.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, decomposition of a surface EMG into contributions of individual MUs enabled analysis of neural coding in relatively large populations of MUs, and, consequentially, many new insights into the neurophysiology of the motor system [1], [3]- [8]. However identification of individual MUs from a surface EMG is not a trivial task.…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed that the CoV of force was smaller (better force steadiness) at the longer length (75 °) than at the shorter length (105 °) of the muscle-tendon unit. Force fluctuations are influenced by the amplitude of the low-frequency oscillations in the neural drive to muscle and the number of MUs, the upper limit of MU recruitment, and their contractile properties [2]. Although MVC force was substantially less at the shorter than the longer length, the target forces were specified relative to the MVC force at each ankle angle.…”
Section: Ankle Angle Did Influence Force Steadinessmentioning
confidence: 99%
“…However, the amplitude of force fluctuations is also influenced by the number of MUs, the upper limit of MU recruitment, and the contractile properties of the MUs [5][6][7]. When several muscles are contributing to the applied force, the amplitude of the force fluctuations depends on the collective properties of these muscles, including the proportion of shared synaptic inputs received by the pools of motor neurons [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When attempting to sustain an isometric contraction, the applied force is never constant but rather fluctuates around an average value (as reviewed in Enoka and Farina, 2021). Typically, force variability is quantified over an entire isometric contraction, usually maintained over several seconds (Laidlaw et al, 2000;Jones et al, 2002;Tracy and Enoka, 2002;Ushiyama et al, 2017).…”
Section: Introductionmentioning
confidence: 99%